Performance index based evaluation of anticoccidials against field strains of Eimeria tenella in broiler chickens - RANA, N; TIKARAM, S M (The Indian Journal of Animal Sciences, 2014)
Amprolium, clopidol, nitrofurazone+ furazolidone and sodium sulphadimethylpyrimidine were evaluated for their performance against 4 field strains of Eimeria tenella isolated from severe outbreaks of coccidiosis at 4 different broiler farms, 2 each at Hisar and lind districts in Haryana state. Day-old hybrid chicks of either sex were challenged with 1 x 105 sporulated oocysts of E. tenella at 3 weeks of age. The drugs were administered to the chicks 24 hr prior to challenge for ascertaining their prophylactic activity. The medication was continued up to 7 days post-challenge. The comparative efficacy of the anticoccidials was evaluated on the basis ofa performance index (PI) based on ratio of mean weight gains, survival and faecal scores of chickens. While the order of drug efficacy at Hisar and lind districts was sodium sulphadimethylpyrimidine followed by amprolium, clopidol and nitrofurazone + furazolidone, the same for find district was clopidol followed by amprolium. sodium sulphadimethylpyrimidine and nitrofurazone + furazolidone.